School-Based Enabling Programs : Creating Opportunity and Connection. - Olds, Anita; Jones, Angela; Sturniolo-Baker, Rebekah; Clarke, Shane; Dawson, Jaimee; McGrath, Wesley; Plumb, Curtis; Schwartz, Catherine; White, Carmel (Student Success v.13 n.3 p.3-10 https://doi.org/10.5204/ssj.2436, 2022)
A growing body of literature and rhetoric from the secondary sector recognises that traditional senior secondary curriculums are not catering to all university aspirational students. This need created an opportunity for University Preparation Pathways (UPP) at Murdoch University to provide a transitional path for an underserviced cohort. FlexiTrack High (FTH), a pioneering school-based enabling program, demonstrates how effective course design can create opportunities for underserviced cohorts, contribute to the Government’s goal of raising tertiary participation rates amongst young people and foster connections between tertiary and secondary institutions. Utilising a second-generation Enabling Transition Pedagogy (ETP), this report explores the pedagogical underpinnings of an effective school-based program. Autoethnographic data obtained through a unique collaboration between Murdoch and partnerships schools, as well as quantitative progression data and student surveys, provide early indicators of the wide range of impacts an explicit model of this nature can have on students and schools. [Author abstract]